Natural products for Gut-X axis: pharmacology, toxicology and microbiology in mycotoxin-caused diseases - Li, Kaiqi; Wang, Shiqi; Qu, Wuyi; Ahmed, Abdelkareem A.; Enneb, Wael; Obeidat, Mohammad Diya’; Liu, Hao-Yu; Dessie, Tadelle; Kim, In Ho; Adam, Saber Y.; Cai, Demin (Frontiers in Pharmacology, 2024)
The gastrointestinal tract serves as a critical defense against external contaminants, comprising a complex system of immunological, physical, chemical, and microbial barriers. Mycotoxins, toxic metabolites from fungi, are present in both animal feed and human food, posing significant health risks. These toxins can disrupt intestinal integrity, alter inflammatory responses, damage the mucus layer, and disrupt bacterial balance. Their toxic effects are diverse, potentially causing damage to the immune system, liver, kidneys, and skin, as well as being linked to cancer, hormonal changes, genetic mutations, bleeding, birth defects, and neurological issues. Targeting gut microbial modulation is an emerging therapeutic strategy. Natural products, rich in polysaccharides, polyphenols, flavonoids, and saponins, exhibit potential anticancer, anti-tumor, antioxidant, immunomodulatory, and antitoxic properties. This review aims to explore the pharmacological, toxicological, and microbiological impacts of natural products on mycotoxicosis, with a focus on the gut-x axis. It also seeks to highlight knowledge gaps and outline future research directions to enhance our understanding of natural products' role in gut-x axis health and mitigate the global health impact of mycotoxin-induced diseases.In general, the GI tract's intestinal barrier serves as a filter for eliminating harmful mycotoxins. Nevertheless, it has been found that a number of mycotoxins cause harm to the gastrointestinal tract. For example, mycotoxins may cause disruption with the normal functioning of the intestinal barrier